Laminate, metal-clad laminate, circuit board, electronic device, electronic equipment, adhesive resin composition, manufacturing method thereof, and adhesive film
Patent Information
- Application Number
- JP2023106629
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
【0022】 本発明の積層体は、厚みが大きく低誘電正接な接着層を内層部に設けるとともに、接着層中にフィラー成分を高濃度に配合することによって引張弾性率及び貯蔵弾性率を適切に制御しているため、厚みムラとラミネート時のシワの発生が抑制されており、優れた誘電特性と難燃性が両立されている。したがって、本発明の積層体を用いた金属張積層板は、例えば、10GHz以上の高周波信号を伝送する回路基板への適用において、伝送損失の低減と、信頼性及び安全性の向上を図ることができる。
Smart Images

Figure 2025006070000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, a metal-clad laminate, a circuit board, an electronic device, and an electronic equipment that are useful as materials for electronic components, as well as an adhesive resin composition, a production method thereof, and an adhesive film. [Background technology]
[0002] In recent years, with the progress of miniaturization, weight reduction, and space saving of electronic devices, there is an increasing demand for flexible printed circuits (FPCs) that are thin, lightweight, flexible, and have excellent durability even when repeatedly bent. Because FPCs allow three-dimensional and high-density mounting even in a limited space, their applications are expanding to include wiring for electronic devices such as HDDs, DVDs, and smartphones, as well as components such as cables and connectors.
[0003] In addition to the increase in density, the performance of devices has improved, and so it is necessary to deal with the higher frequencies of transmission signals. When transmitting high-frequency signals, if the transmission loss in the transmission path is large, inconveniences such as loss of electrical signals and long signal delay times occur. In order to deal with the higher frequencies of transmission signals, a proposal has been made to improve dielectric properties by interposing an adhesive layer with a large thickness ratio between the insulating resin layers of a pair of single-sided metal-clad laminates, and using a thermoplastic polyimide made from dimer acid diamine (DDA) in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups as the material for the adhesive layer (Patent Document 1). In order to further improve the dielectric properties in the layer structure as in Patent Document 1, it is effective to increase the thickness of the inner layer portion consisting of the adhesive layer with excellent dielectric properties and increase the thickness ratio to the entire resin layer. However, increasing the thickness of the inner layer containing aliphatic compounds with low polarity and increasing the thickness ratio to the entire resin layer reduces flame retardancy, which has been a bottleneck in further improving the dielectric properties. Furthermore, if the thickness of the inner layer portion is large, unevenness in thickness is likely to occur during coating, and if this unevenness in thickness is large, the characteristic impedance will vary greatly, resulting in adverse effects such as increased loss of transmission signals. Furthermore, when laminating a long adhesive film and a single-sided metal-clad laminate using a roll-to-roll method or the like, there was an issue that the adhesive film was too soft, and wrinkles were easily generated due to the shear stress during lamination. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-170417 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a laminate which has excellent dielectric properties and flame retardancy suitable for use in high frequency circuit boards, and which suppresses unevenness in the thickness of the adhesive layer and the occurrence of wrinkles during lamination. [Means for solving the problem]
[0006] As a result of intensive research, the inventors of the present invention have focused on the fluidity of the adhesive varnish, the tensile modulus of the adhesive film, and the storage modulus at the lamination temperature as factors that cause uneven thickness of the adhesive layer and wrinkles during lamination. They have found that by providing an adhesive layer with a large thickness and a low dielectric tangent as an inner layer and by blending a high concentration of a filler component in the adhesive layer to appropriately control the tensile modulus and storage modulus, uneven thickness and wrinkles during lamination can be improved, and the dielectric tangent can be reduced while maintaining excellent flame retardancy, and thus the present invention has been completed.
[0007] That is, the laminate of the first aspect of the present invention is a laminate comprising a first insulating resin layer, a second insulating resin layer, and an adhesive layer laminated between the first insulating resin layer and the second insulating resin layer so as to abut against the first insulating resin layer and the second insulating resin layer. In the laminate of the first aspect of the present invention, a total thickness T1 of the first insulating resin layer, the adhesive layer, and the second insulating resin layer is within a range of 70 to 500 μm, a thickness T2 of the adhesive layer is within a range of more than 50 μm and not more than 450 μm, and a ratio of T2 to T1 (T2 / T1) is within a range of more than 0.5 and not more than 0.96. In addition, the laminate according to the first aspect of the present invention is characterized in that the adhesive layer contains a resin component and a filler component, The resin component contains a polyimide having tetracarboxylic acid residues derived from a tetracarboxylic acid anhydride component and diamine residues derived from a diamine component, and the polyimide contains 40 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues. In addition, in the laminate of the first aspect of the present invention, the filler component contains a metal salt of an organic phosphinic acid, and the weight ratio of the filler component to 100 parts by weight of the total amount of the resin component is in the range of more than 40 parts by weight and not more than 90 parts by weight.
[0008] In the laminate of the first aspect of the present invention, when a thickness direction cross section of the adhesive layer is observed under a scanning electron microscope, the total area ratio of filler components having a particle size exceeding 10 μm and filler missing parts having a major axis exceeding 10 μm within a surface field of 100 μm x 100 μm may be 1% or less, on average, over any 10 points within the surface field of 100 μm x 100 μm.
[0009] In the laminate of the first aspect of the present invention, the polyimide may be a polyimide having a ketone group in the molecule, and the resin component may contain a crosslinking agent having a functional group that undergoes a nucleophilic reaction with the ketone group.
[0010] In the laminate according to the first aspect of the present invention, the polyimide may form a crosslinked structure by a reaction between a polyimide having a ketone group in the molecule and a crosslinking agent having a functional group which undergoes a nucleophilic reaction with the ketone group.
[0011] In the laminate according to the first aspect of the present invention, the adhesive layer may have a tensile modulus within the range of 1.0 GPa or more and 1.2 GPa or less.
[0012] In the laminate according to the first aspect of the present invention, the adhesive layer may have a storage modulus at 80° C. in the range of 10 MPa or more and 20 MPa or less.
[0013] In the laminate according to the first aspect of the present invention, the first insulating resin layer and the second insulating resin layer may be a multi-layer polyimide layer having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer. In this case, the multi-layer polyimide layer may have an outermost layer being a thermoplastic polyimide layer.
[0014] The laminate according to the first aspect of the present invention may be in the form of a long sheet, with a length in the width direction (TD) being within the range of 0.2 m or more and 2.0 m or less.
[0015] A metal-clad laminate according to a second aspect of the present invention comprises the laminate according to the first aspect above, and a metal layer laminated on one or both sides of the laminate.
[0016] A circuit board according to a third aspect of the present invention comprises the laminate according to the first aspect above, and a wiring layer laminated on one or both sides of the laminate.
[0017] An electronic device according to a fourth aspect of the present invention comprises the circuit board according to the third aspect.
[0018] An electronic device according to a fifth aspect of the present invention comprises the circuit board according to the third aspect.
[0019] An adhesive resin composition according to a sixth aspect of the present invention is an adhesive resin composition containing a resin component, a filler component and an organic solvent. In addition, an adhesive resin composition according to a sixth aspect of the present invention comprises a polyimide in which the resin component has tetracarboxylic acid residues derived from a tetracarboxylic acid anhydride component and diamine residues derived from a diamine component, and the diamine residues comprise 40 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues. In addition, in an adhesive resin composition according to a sixth aspect of the present invention, the filler component contains a metal salt of an organic phosphinic acid, and the weight ratio of the filler component to 100 parts by weight of the total amount of the resin components is in the range of more than 40 parts by weight and not more than 90 parts by weight. In addition, the adhesive resin composition according to the sixth aspect of the present invention, when formed into a film with a thickness in the range of more than 50 μm and not more than 450 μm, has a tensile modulus in the range of 1.0 GPa or more and 1.2 GPa or less, and a storage modulus at 80° C. in the range of 10 MPa or more and 20 MPa or less.
[0020] A method for producing an adhesive resin composition according to a seventh aspect of the present invention is a method for producing the adhesive resin composition according to the sixth aspect. A method for producing an adhesive resin composition according to a seventh aspect of the present invention includes the following steps (i) and (ii); (i) mixing and stirring a portion of the resin component and the filler component in an organic solvent to obtain a filler dispersion; and (ii) a step of mixing the remainder of the resin component with an organic solvent into the filler dispersion and stirring the mixture to obtain the adhesive resin composition; Contains: In addition, in the seventh aspect of the present invention, the method for producing an adhesive resin composition comprises adjusting, in step (i), the weight ratio of the resin content in the filler dispersion to within the range of 3 to 15 parts by weight relative to 100 parts by weight of a final total amount of the resin content, and adjusting the solids concentration in the filler dispersion to within the range of 40 to 60 parts by weight, and adjusting, in step (ii), the weight ratio of the filler component in the adhesive resin composition to within the range of more than 40 parts by weight and not more than 90 parts by weight relative to 100 parts by weight of a final total amount of the resin content.
[0021] An adhesive film according to an eighth aspect of the present invention is an adhesive film containing a resin component and a filler component. An adhesive film according to an eighth aspect of the present invention comprises a polyimide in which the resin component has tetracarboxylic acid residues derived from a tetracarboxylic acid anhydride component and diamine residues derived from a diamine component, and the polyimide contains 40 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which the two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues. In addition, in an adhesive film according to an eighth aspect of the present invention, the filler component contains a metal salt of an organic phosphinic acid, and the weight ratio of the filler component to 100 parts by weight of the total amount of the resin component is in the range of more than 40 parts by weight and not more than 90 parts by weight. In addition, the adhesive film of the eighth aspect of the present invention has a thickness in the range of more than 50 μm and not more than 450 μm, a tensile modulus in the range of 1.0 GPa or more and 1.2 GPa or less, and a storage modulus at 80° C. in the range of 10 MPa or more and 20 MPa or less. Effect of the Invention
[0022] The laminate of the present invention has an inner layer having a large thickness and a low dielectric loss tangent, and the adhesive layer contains a high concentration of a filler component to appropriately control the tensile modulus and storage modulus, thereby suppressing unevenness in thickness and the occurrence of wrinkles during lamination, and achieving both excellent dielectric properties and flame retardancy. Therefore, when applied to a circuit board that transmits high-frequency signals of 10 GHz or more, a metal-clad laminate using the laminate of the present invention can reduce transmission loss and improve reliability and safety. [Brief description of the drawings]
[0023] [Figure 1] 1 is a schematic cross-sectional view showing a layer structure of a laminate according to a preferred embodiment of the present invention. [Diagram 2]FIG. 2 is a schematic cross-sectional view showing a layer structure of a laminate according to another preferred embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing a layer structure of a metal-clad laminate according to a preferred embodiment of the present invention. [Figure 4] FIG. 2 is a schematic cross-sectional view showing a layer structure of a metal-clad laminate according to another preferred embodiment of the present invention. [Diagram 5] 1 is a scanning electron microscope image of a cross section of the adhesive layer sheet obtained in Example 5. [Figure 6] 1 is a scanning electron microscope image of a cross section of the adhesive layer sheet obtained in Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of the present invention will be described with reference to the accompanying drawings.
[0025] [Laminate] The laminate according to one embodiment of the present invention is a laminate in which a first insulating resin layer, an adhesive layer, and a second insulating resin layer are laminated in this order. By interposing an adhesive layer with a low dielectric tangent between two insulating resin layers to make the film thick, a laminate (laminated resin film) with a low dielectric tangent and a large thickness is obtained. In addition, by sandwiching the adhesive layer, which has a large dimensional change, between insulating resin layers, which have a small dimensional change, dimensional stability can be ensured. Furthermore, by sandwiching the adhesive layer between two insulating resin layers, moisture absorption and water absorption of the adhesive layer is suppressed, and deterioration of the dielectric tangent is mitigated.
[0026] 1 shows a cross-sectional structure of a laminate 100 according to a preferred embodiment of the present invention. The laminate 100 has a layer structure in which a thermoplastic polyimide layer 10A / a non-thermoplastic polyimide layer 20A / a thermoplastic polyimide layer 30A / an adhesive layer AD / a thermoplastic polyimide layer 30B / a non-thermoplastic polyimide layer 20B / a thermoplastic polyimide layer 10B are laminated in this order. Here, the thermoplastic polyimide layer 10A, the non-thermoplastic polyimide layer 20A, and the thermoplastic polyimide layer 30A constitute a first insulating resin layer 40A, and the thermoplastic polyimide layer 10B, the non-thermoplastic polyimide layer 20B, and the thermoplastic polyimide layer 30B constitute a second insulating resin layer 40B. Therefore, the laminate 100 has a structure in which the first insulating resin layer 40A, the adhesive layer AD, and the second insulating resin layer 40B are laminated in this order.
[0027] FIG. 2 shows a cross-sectional structure of a laminate 101 according to another preferred embodiment of the present invention. The laminate 101 has a layer structure in which a thermoplastic polyimide layer 10A / a non-thermoplastic polyimide layer 20A / an adhesive layer AD / a non-thermoplastic polyimide layer 20B / a thermoplastic polyimide layer 10B are laminated in this order. Here, the thermoplastic polyimide layer 10A and the non-thermoplastic polyimide layer 20A constitute a first insulating resin layer 40A, and the thermoplastic polyimide layer 10B and the non-thermoplastic polyimide layer 20B constitute a second insulating resin layer 40B. Therefore, the laminate 101 has a structure in which the first insulating resin layer 40A, the adhesive layer AD, and the second insulating resin layer 40B are laminated in this order.
[0028] In the configuration example shown in FIG. 1 and FIG. 2, the thermoplastic polyimide layer 10A and the thermoplastic polyimide layer 10B of the outermost layer have a function of ensuring adhesion when a metal layer is laminated. The non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B have a function of ensuring dimensional stability. The multiple thermoplastic polyimide layers 10A, 10B, 30A, and 30B may be composed of the same or different types of thermoplastic polyimide. The non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B may also be composed of the same or different types of non-thermoplastic polyimide. Details of the preferred polyimide used for the first insulating resin layer 40A and the second insulating resin layer 40B will be described later. The first insulating resin layer 40A and the second insulating resin layer 40B may contain, as appropriate, plasticizers, curable resin components such as epoxy resins, curing agents, curing accelerators, organic or inorganic fillers, coupling agents, flame retardants, and the like.
[0029] <Insulating resin layer> The first insulating resin layer 40A and the second insulating resin layer 40B may each be a single layer or a laminate of multiple resin layers. The resin constituting the first insulating resin layer 40A and the second insulating resin layer 40B is not particularly limited as long as it is a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenol resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, and ETFE, but is preferably composed of polyimide.
[0030] <Adhesive layer> The adhesive layer AD contains a resin component and a filler component. Resin content: The resin component contains a polyimide (hereinafter, sometimes referred to as "adhesive polyimide") that has tetracarboxylic acid residues derived from a tetracarboxylic anhydride component and diamine residues derived from a diamine component, and contains 40 mol% or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues. Details of the adhesive polyimide will be described later. The resin component also contains a crosslinking agent, which will be described later.
[0031] Filler Ingredients: The filler component contains a metal salt of an organic phosphinic acid. The metal salt of an organic phosphinic acid is a flame retardant that does not deteriorate the dielectric properties of the polyimide. In order to fully exert the effects of the invention, preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight of the filler component is a metal salt of an organic phosphinic acid. As the metal salt of an organic phosphinic acid, for example, an aluminum salt of an organic phosphinic acid represented by the following general formula (F1) is preferable.
[0032] [ka]
[0033] In the general formula (F1), two R's each independently represent an alkyl group, and R is preferably a lower alkyl group having 1 to 4 carbon atoms.
[0034] In addition, the metal salt of organic phosphinic acid has a mean particle diameter (D 50 ) is preferably within the range of 1.0 to 3.0 μm, and the ratio of particles having a particle diameter exceeding 10 μm is 1 vol % or less. If the ratio of particles having a particle diameter exceeding 10 μm exceeds 1 vol %, the filler particle diameter in the adhesive layer AD becomes large, and the filler becomes likely to fall off during cutting or drilling. As the metal salt of the above-mentioned organic phosphinic acid, commercially available products can be used, for example, Exolit OP945 (trade name, manufactured by Clariant).
[0035] From the viewpoint of ensuring the flame retardancy of the adhesive layer AD and exhibiting a tensile modulus and storage modulus capable of suppressing the occurrence of wrinkles during thermocompression bonding with the insulating resin layer, the weight ratio of the filler component to the total amount of 100 parts by weight of the resin components is within the range of more than 40 parts by weight and not more than 90 parts by weight, preferably within the range of more than 40 parts by weight and not more than 80 parts by weight, and more preferably within the range of 45 parts by weight to 70 parts by weight. If the weight ratio of the filler component is 40 parts by weight or less, not only is the flame retardant effect not fully exhibited, but wrinkles are likely to occur during thermocompression bonding with the insulating resin layer, and if it exceeds 90 parts by weight, the elongation of the adhesive layer AD may decrease or the dielectric properties may deteriorate. In addition, when the concentration of the particulate filler component is increased in order to improve flame retardancy, aggregation occurs, and therefore it becomes necessary to compound a large amount of dispersant. However, since the dispersant has an adverse effect on the dielectric properties, it has been difficult to achieve both low dielectric tangent and improved flame retardancy. In the present invention, as described below, in the process of producing an adhesive resin composition, the polyimide and the filler component are mixed in multiple stages, thereby realizing a high concentration compounding of the filler component of more than 40 parts by weight per 100 parts by weight of the total amount of the resin without necessarily using a dispersant.
[0036] In order to fully exert the effects of the present invention, the total amount of the resin component and the filler component is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight, based on the total solid content in the adhesive layer AD. In the present invention, the "solid content" means the remainder excluding the solvent.
[0037] In addition, in the adhesive layer AD, the total area ratio of filler components having a particle diameter of more than 10 μm and filler-dropped parts having a major axis of more than 10 μm is preferably 1% or less, more preferably 0.5% or less, and most preferably 0.1 to 0%, on average in any 10 points of the surface field of view within 100 μm × 100 μm when the cross section in the thickness direction is observed with a scanning electron microscope, more preferably 0.5% or less, and most preferably 0.1 to 0%. In this case, "particle diameter" means the major axis (the maximum diameter) when the planar shape in the scanning electron microscope observation is other than a perfect circle. In addition, "filler-dropped parts" are observed as voids that are traces of fallen filler components having a particle diameter of more than 10 μm when the cross section in the thickness direction is observed with a scanning electron microscope, and the major axis of the voids exceeds 10 μm. If the combined area ratio of coarse filler components with particle diameters exceeding 10 μm and fallen filler parts with long diameters exceeding 10 μm exceeds 1% on average, the fall-off of filler components will be likely to occur or may have already occurred, raising concerns about the generation of foreign matter during the circuit processing process and poor through-hole plating during drilling.
[0038] The adhesive layer AD preferably has desired properties such as low dielectric tangent in addition to adhesiveness. For example, when the adhesive layer AD is applied to a circuit board, the dielectric tangent at 10 GHz is preferably 0.003 or less, more preferably 0.0027 or less, and even more preferably 0.0025 or less under moisture-controlled conditions in order to suppress deterioration of dielectric loss, and is preferably 0.007 or less, more preferably 0.006 or less, and even more preferably 0.005 or less under moisture-absorption conditions. If the dielectric tangent at 10 GHz of the adhesive layer AD exceeds 0.003 under moisture-controlled conditions, inconveniences such as loss of electrical signals on the transmission path of high-frequency signals are likely to occur when the adhesive layer AD is applied to a circuit board. In addition, if the dielectric tangent at 10 GHz of the adhesive layer AD exceeds 0.007 under moisture-absorption conditions, it is easily affected by environmental humidity, and transmission loss is likely to occur depending on the usage environment when applied to a circuit board. The moisture-controlled conditions and moisture-absorption conditions refer to the conditions of "moisture-controlled" and "water-absorbed" described in the examples below.
[0039] In addition, in order to ensure impedance matching when applied to a circuit board, the adhesive layer AD preferably has a relative dielectric constant of 4.0 or less at 10 GHz. If the relative dielectric constant of the adhesive layer AD exceeds 4.0 at 10 GHz, the adhesive layer AD may have a deteriorated dielectric loss when applied to a circuit board, which may easily cause inconveniences such as loss of electrical signals on the transmission path of high-frequency signals.
[0040] The adhesive layer AD may have an average thermal expansion coefficient of more than 30 ppm / K in the in-plane direction perpendicular to the thickness direction from 250° C. to 100° C. Since the adhesive layer AD has low elasticity, it can alleviate internal stress generated during lamination even if the average thermal expansion coefficient in the in-plane direction exceeds 30 ppm / K.
[0041] From the viewpoint of effectively suppressing the occurrence of wrinkles during thermocompression bonding with the insulating resin layer, the adhesive layer AD preferably has a tensile modulus of elasticity in the range of 1.0 GPa to 1.2 GPa, more preferably in the range of 1.0 GPa to 1.1 GPa. If the tensile modulus of elasticity of the adhesive layer AD is less than 1.0 GPa, wrinkles are likely to occur during thermocompression bonding with the insulating resin layer, and if it exceeds 1.2 GPa, adhesion with the insulating resin layer decreases, and air bubbles are likely to enter between the adhesive layer AD and the insulating resin layer.
[0042] Similarly, from the viewpoint of effectively suppressing the occurrence of wrinkles during thermocompression bonding with the insulating resin layer, the storage modulus of the adhesive layer AD at 80° C. is preferably in the range of 10 MPa to 20 MPa, more preferably in the range of 13 MPa to 17 MPa. The temperature of 80° C. is assumed to be the thermocompression bonding temperature, and if the storage modulus of the adhesive layer AD at this temperature is less than 10 MPa, wrinkles are likely to occur during thermocompression bonding with the insulating resin layer, and if it exceeds 20 MPa, the adhesion is reduced.
[0043] <Layer thickness> When the total thickness T1 of the first insulating resin layer 40A, the adhesive layer AD, and the second insulating resin layer 40B is T1, the total thickness T1 of the laminates 100 and 101 is in the range of 70 to 500 μm, and preferably in the range of 100 to 300 μm. If the total thickness T1 is less than 70 μm, the effect of reducing the transmission loss when used in a circuit board becomes insufficient, and if it exceeds 500 μm, there is a risk of reduced productivity. In addition, a thickness of 70 μm or more is difficult to achieve with a single layer, but the laminates 100 and 101 achieve such a thickness by using a characteristic laminate structure.
[0044] Also, the thickness T2 of the adhesive layer AD is greater than 50 μm. The effect of the present invention, namely, compatibility between excellent dielectric properties and flame retardancy, is particularly effective in a laminate structure in which the thickness T2 of the adhesive layer AD having a low dielectric tangent is large. From this viewpoint, the thickness T2 of the adhesive layer AD is, for example, in the range of more than 50 μm to 450 μm, and more preferably in the range of more than 50 μm to 250 μm. If the thickness T2 of the adhesive layer AD is less than the above lower limit, the dielectric tangent is insufficient, and problems such as insufficient dielectric properties can occur. On the other hand, if the thickness T2 of the adhesive layer AD exceeds the above upper limit, problems such as difficulty in ensuring flame retardancy and reduced dimensional stability can occur.
[0045] In addition, the effect of the present invention of achieving both excellent dielectric properties and flame retardancy is particularly effective in a laminate structure in which the ratio of the thickness T2 of the adhesive layer AD is large, so the ratio (T2 / T1) of the thickness T2 of the adhesive layer AD to the total thickness T1 is preferably in the range of more than 0.5 to 0.96, more preferably more than 0.5 to 0.75. If the ratio (T2 / T1) is 0.5 or less, the dielectric loss tangent is insufficient and sufficient dielectric properties cannot be obtained. If it exceeds 0.96, it becomes difficult to ensure flame retardancy, dimensional stability is reduced, and other problems occur.
[0046] The thickness T3 of the first insulating resin layer 40A and the second insulating resin layer 40B is preferably in the range of 10 to 50 μm, and more preferably in the range of 12 to 25 μm. If the thickness T3 of each of the first insulating resin layer 40A and the second insulating resin layer 40B is less than the above lower limit, problems such as warping of the laminates 100 and 101 may occur. If the thickness T3 of the first insulating resin layer 40A and the second insulating resin layer 40B exceeds the above upper limit, problems such as a decrease in transmission characteristics when used as a circuit board may occur. The first insulating resin layer 40A and the second insulating resin layer 40B may have the same thickness or different thicknesses. The thermoplastic polyimide layers 10A, 10B, 30A, and 30B may also have the same thickness or different thicknesses, and the non-thermoplastic polyimide layers 20A and 20B may have the same thickness or different thicknesses.
[0047] <Dielectric tangent> In order to suppress deterioration of dielectric loss when applied to, for example, a circuit board, the laminates 100 and 101 have a dielectric loss tangent at 10 GHz measured using an SPDR resonator, preferably 0.005 or less, more preferably 0.004 or less, and even more preferably 0.003 or less, under moisture-controlled conditions, and preferably 0.008 or less, more preferably 0.007 or less, and even more preferably 0.006 or less, under moisture-absorbed conditions. If the dielectric loss tangent at 10 GHz of the laminates 100 and 101 exceeds 0.005 under moisture-controlled conditions, problems such as loss of electrical signals on the transmission path of high-frequency signals are likely to occur when applied to a circuit board. If the dielectric loss tangent at 10 GHz of the laminates 100 and 101 exceeds 0.008 under moisture-absorbed conditions, the laminates 100 and 101 are susceptible to the influence of environmental humidity, and transmission loss is likely to occur depending on the usage environment when applied to a circuit board. The moisture-controlled conditions and moisture-absorbed conditions refer to the conditions of "moisture-controlled" and "moisture-absorbed" described in the examples below.
[0048] <Dielectric constant> When the laminates 100 and 101 are applied as an insulating layer of a circuit board, for example, the insulating layer as a whole preferably has a relative dielectric constant of 3.5 or less at 10 GHz measured using an SPDR resonator in order to ensure impedance matching. If the relative dielectric constant of the laminates 100 and 101 at 10 GHz exceeds 3.5, when the laminates are applied to a circuit board, this leads to deterioration of the dielectric loss of the first insulating resin layer 40A and the second insulating resin layer 40B, and is likely to cause inconveniences such as loss of electrical signals on the transmission path of high-frequency signals.
[0049] The laminates 100 and 101 have a length L in the width direction (TD direction). TD is in the range of 0.2 m or more and 2.0 m or less, and the length L TD Length L in the longitudinal direction (MD direction) MD Ratio (L MD / L TD ) is preferably in a long shape, for example, 25 or more, preferably in a range of 50 to 5000. By having the laminates 100, 101 in a long shape, the effect of suppressing uneven thickness and wrinkles that tend to occur when the laminates are manufactured by a method such as roll-to-roll can be maximized.
[0050] <Polyimide> Next, polyimide, which is a preferred resin constituting the first insulating resin layer 40A, the second insulating resin layer 40B, and the adhesive layer AD, will be described. Polyimide is obtained by reacting a tetracarboxylic anhydride component with a diamine component containing an aliphatic diamine and / or an aromatic diamine, and contains a tetracarboxylic acid residue derived from the tetracarboxylic anhydride component and a diamine residue derived from the diamine component. In the present invention, the "tetracarboxylic acid residue" refers to a tetravalent group derived from a tetracarboxylic dianhydride, and the "diamine residue" refers to a divalent group derived from a diamine compound. When the raw materials tetracarboxylic dianhydride and diamine compound are reacted in approximately equal moles, the types and molar ratios of the tetracarboxylic acid residues and diamine residues contained in the polyimide can be approximately corresponding to the types and molar ratios of the raw materials. In the present invention, the term "polyimide" refers to a resin made of a polymer having an imide group in the molecular structure, such as polyimide, polyamideimide, polyetherimide, polyesterimide, polysiloxaneimide, polybenzimidazoleimide, etc. In addition, when the polyimide has a plurality of structural units, they may exist as blocks or randomly, but it is preferable that they exist randomly. In addition, the term "thermoplastic polyimide" generally refers to a polyimide whose glass transition temperature (Tg) can be clearly confirmed. In the present invention, however, the term "thermoplastic polyimide" refers to a polyimide whose storage modulus at 30°C measured using a dynamic mechanical analyzer (DMA) is 1.0×10 8 Pa or more, and the storage modulus at 300°C is 3.0×10 7 The term "non-thermoplastic polyimide" generally refers to a polyimide that does not soften or exhibit adhesiveness even when heated. In the present invention, however, the term "non-thermoplastic polyimide" refers to a polyimide having a storage modulus of 1.0×10 Pa at 30° C. as measured using a dynamic viscoelasticity measuring device (DMA). 9 Pa or more, and the storage modulus at 300°C is 3.0×10 8 This refers to polyimides with a modulus of tensile strength (MPa) or higher.
[0051] <Thermoplastic polyimide> The thermoplastic polyimide for forming the thermoplastic polyimide layers 10A, 10B, 30A, and 30B in the first insulating resin layer 40A and the second insulating resin layer 40B can control thermal expansion, adhesion, glass transition temperature, and the like by selecting the types of tetracarboxylic anhydride components and diamine components as raw materials, and the respective molar ratios when two or more types of acid anhydrides or diamines are used. As the tetracarboxylic anhydride components and diamine components as raw materials, monomers generally used in the synthesis of thermoplastic polyimides can be used, but in order to improve flame retardancy, it is preferable to use aromatic tetracarboxylic dianhydrides or aromatic diamines.
[0052] Examples of aromatic tetracarboxylic dianhydrides include pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic monoester acid anhydride) (TAHQ), and ethylene glycol. Aromatic tetracarboxylic dianhydrides such as bis-anhydrotrimellitate (TMEG), 2,3,6,7-naphthalenetetracarboxylic dianhydride (NTCDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,3',3,4'-biphenyltetracarboxylic dianhydride, and 2,2',3,3'-biphenyltetracarboxylic dianhydride can be preferably used. In order to impart sufficient flame retardancy to the laminates 100, 101, the thermoplastic polyimide layers 30A, 30B preferably contain a total of 50 to 100 molar parts, and more preferably 60 to 100 molar parts, of tetracarboxylic acid residues derived from one or more of the above aromatic tetracarboxylic dianhydrides per 100 molar parts of all tetracarboxylic acid residues.
[0053] Examples of aromatic diamines include 1,4-diaminobenzene (p-PDA), 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), bis[4-(4-aminophenoxy)phenyl]ketone (BAPK), bis[4- (3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis( 4-aminophenoxy)benzene, bisanilinefluorene (BAFL), 9,9-bis(4-amino-3-chlorophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-fluorophenyl)fluorene, 4,4''-diamino-para-terphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-diethyl-4,4'-diaminobiphenyl (m-EB), 2,2'-diethoxy-4,4'-diaminobiphenyl (m- Preferred examples of aromatic diamines that can be used include 2,2'-dipropoxy-4,4'-diaminobiphenyl (m-POB), 2,2'-di-n-propyl-4,4'-diaminobiphenyl (m-NPB), 2,2'-divinyl-4,4'-diaminobiphenyl (VAB), 4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB), 4,4'-diamino-2,2',5,5'-tetrachlorobiphenyl, and 4,4'-diaminooctafluorobiphenyl. In order to impart sufficient flame retardancy to the laminates 100, 101, the thermoplastic polyimide layers 10A, 10B, 30A, 30B preferably contain a total of 50 to 100 molar parts, and more preferably 60 to 100 molar parts, of diamine residues derived from one or more of the above aromatic diamines per 100 molar parts of all diamine residues.
[0054] <Non-thermoplastic polyimide> The non-thermoplastic polyimide for forming the non-thermoplastic polyimide layers 20A, 20B in the first insulating resin layer 40A and the second insulating resin layer 40B can have thermal expansion properties, dielectric properties, etc. controlled by selecting the types of tetracarboxylic anhydride components and diamine components as raw materials, and the respective molar ratios when two or more types of acid anhydrides or diamines are used. As the tetracarboxylic anhydride components and diamine components as raw materials, monomers generally used in the synthesis of non-thermoplastic polyimides can be used, but in order to improve flame retardancy, it is preferable to use aromatic tetracarboxylic dianhydrides and aromatic diamines exemplified in the above description of thermoplastic polyimides.
[0055] In addition, in order to impart sufficient flame retardancy to the laminates 100, 101, the non-thermoplastic polyimide layers 20A, 20B preferably contain a total of 50 to 100 molar parts, and more preferably 60 to 100 molar parts, of tetracarboxylic acid residues derived from one or more of the aromatic tetracarboxylic dianhydrides exemplified in the description of the thermoplastic polyimides, relative to 100 molar parts of all tetracarboxylic acid residues. Furthermore, in order to impart sufficient flame retardancy to the laminates 100, 101, the non-thermoplastic polyimide layers 20A, 20B preferably contain a total of 50 to 100 molar parts, and more preferably 60 to 100 molar parts, of diamine residues derived from one or more of the aromatic diamines exemplified in the description of the thermoplastic polyimides above, per 100 molar parts of all diamine residues.
[0056] <Adhesive polyimide> The adhesive polyimide is the main component of the resin content contained in the adhesive layer AD. The main component of the resin content means a component contained in more than 50% by weight of the total resin content. In order to fully exert the effects of the invention, the resin content preferably contains 70% by weight or more of adhesive polyimide, more preferably 80% by weight or more, and most preferably 90% by weight or more.
[0057] (Tetracarboxylic acid residue) The adhesive polyimide may contain, without particular limitation, tetracarboxylic acid residues derived from tetracarboxylic dianhydrides generally used in thermoplastic polyimides, but preferably contains a total of 90 molar parts or more, and more preferably 95 molar parts or more, of tetracarboxylic acid residues derived from tetracarboxylic dianhydrides represented by the following general formula (1) (hereinafter, sometimes referred to as "tetracarboxylic acid residues (1)") relative to 100 molar parts of all tetracarboxylic acid residues. By containing 90 molar parts or more of tetracarboxylic acid residues (1) relative to 100 molar parts of all tetracarboxylic acid residues, it is easy to achieve both flexibility and heat resistance of the adhesive polyimide, which is preferable. If the total amount of tetracarboxylic acid residues (1) is less than 90 molar parts, the solvent solubility of the adhesive polyimide tends to decrease.
[0058] [ka]
[0059] In general formula (1), X represents a single bond or a divalent group selected from the following formulae:
[0060] [ka]
[0061] In the above formula, Z represents -C6H4-, -(CH2)n-, or -CH2-CH(-OC(=O)-CH3)-CH2-, where n represents an integer of 1 to 20.
[0062] Examples of tetracarboxylic acid dianhydrides for deriving the tetracarboxylic acid residue (1) include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic acid monoester anhydride) (TAHQ), and ethylene glycol bisanhydrotrimellitate (TMEG).
[0063] The adhesive polyimide may contain a tetracarboxylic acid residue derived from an acid dianhydride other than the tetracarboxylic acid dianhydride represented by the above general formula (1) within a range that does not impair the effects of the invention. There are no particular limitations on such tetracarboxylic acid residue, but it is preferable to use the aromatic tetracarboxylic acid dianhydrides exemplified in the description of the thermoplastic polyimide above.
[0064] (Diamine residue) The adhesive polyimide contains 40 mol% or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues. If the content of the diamine residues derived from the dimer diamine composition is less than 40 mol% relative to the total diamine residues, the polar groups contained in the adhesive polyimide increase relatively, so that the dielectric constant and dielectric loss tangent tend to increase, making it difficult to reduce the dielectric loss tangent of the adhesive layer AD, and the adhesive layer AD cannot obtain the adhesiveness required for the adhesive layer AD. By setting the content of the diamine residues derived from the dimer diamine composition to 40 mol% or more, the dielectric constant and dielectric loss tangent of the adhesive layer AD can be sufficiently reduced, and the adhesive polyimide can be made solvent-soluble. From this viewpoint, the content of the diamine residues derived from the dimer diamine composition is preferably 60 mol% or more, more preferably 80 mol% or more, and most preferably within the range of 90 to 100 mol% relative to the total diamine residues.
[0065] The dimer diamine composition is a refined product containing the following component (a) as a main component with the amounts of components (b) and (c) being controlled.
[0066] (a) dimer diamine; The dimer diamine of the component (a) means a diamine in which two terminal carboxylic acid groups (-COOH) of a dimer acid are replaced by primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids, and its industrial production process is almost standardized in the industry, and is obtained by dimerizing unsaturated fatty acids having 11 to 22 carbon atoms using a clay catalyst or the like. Industrially obtained dimer acid is mainly composed of a dibasic acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid, linoleic acid, and linolenic acid, but contains any amount of monomer acid (having 18 carbon atoms), trimer acid (having 54 carbon atoms), and other polymerized fatty acids having 20 to 54 carbon atoms depending on the degree of purification. In addition, although double bonds remain after the dimerization reaction, in the present invention, those which have been further subjected to a hydrogenation reaction to reduce the degree of unsaturation are also included in the dimer acid. The dimer diamine of component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having 18 to 54 carbon atoms, preferably 22 to 44 carbon atoms, with a primary aminomethyl group or an amino group.
[0067] As a feature of dimer diamine, it is possible to impart characteristics derived from the skeleton of dimer acid. That is, since dimer diamine is an aliphatic macromolecule with a molecular weight of about 560 to 620, it is possible to increase the molar volume of the molecule and relatively reduce the polar group of the polyimide. It is considered that such a feature of dimer diamine contributes to improving the dielectric properties by reducing the relative dielectric constant and dielectric tangent while suppressing the deterioration of the heat resistance of the adhesive polyimide. In addition, since it has two freely moving hydrophobic chains with 7 to 9 carbon atoms and two chain-like aliphatic amino groups with a length close to 18 carbon atoms, it is not only possible to impart flexibility to the polyimide, but also possible to make the polyimide have an asymmetric chemical structure or a non-planar chemical structure, and therefore it is considered that it is possible to reduce the dielectric constant of the polyimide.
[0068] The dimer diamine composition used may be one in which the dimer diamine content of component (a) is increased to 96% by weight or more, preferably 97% by weight or more, more preferably 98% by weight or more by a purification method such as molecular distillation. By increasing the dimer diamine content of component (a) to 96% by weight or more, the broadening of the molecular weight distribution of the polyimide can be suppressed. If technically possible, it is best that the entire dimer diamine composition (100% by weight) is composed of component (a) dimer diamine.
[0069] (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; The monobasic acid compound having 10 to 40 carbon atoms is a mixture of a monobasic unsaturated fatty acid having 10 to 20 carbon atoms derived from the raw material of dimer acid, and a monobasic acid compound having 21 to 40 carbon atoms which is a by-product during the production of dimer acid. The monoamine compound is obtained by substituting the terminal carboxylic acid group of these monobasic acid compounds with a primary aminomethyl group or an amino group.
[0070] The monoamine compound (b) is a component that suppresses an increase in the molecular weight of the polyimide. During polymerization of the polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal acid anhydride group of the polyamic acid or polyimide to cap the terminal acid anhydride group, thereby suppressing an increase in the molecular weight of the polyamic acid or polyimide.
[0071] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms is a polybasic acid compound mainly composed of a tribasic acid compound having 41 to 80 carbon atoms, which is a by-product during the production of dimer acid. It may also contain a polymerized fatty acid other than dimer acid having 41 to 80 carbon atoms. The amine compound is obtained by substituting the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.
[0072] The amine compound (c) is a component that promotes an increase in the molecular weight of the polyimide. The trifunctional or higher amino group, the main component of which is a triamine derived from a trimer acid, reacts with the terminal acid anhydride group of the polyamic acid or polyimide, rapidly increasing the molecular weight of the polyimide. In addition, amine compounds derived from polymerized fatty acids other than dimer acids having 41 to 80 carbon atoms also increase the molecular weight of the polyimide, causing gelation of the polyamic acid or polyimide.
[0073] When each component is quantified by measurement using gel permeation chromatography (GPC), in order to easily confirm the peak start, peak top, and peak end of each component of the dimer diamine composition, a sample of the dimer diamine composition treated with acetic anhydride and pyridine is used, and cyclohexanone is used as an internal standard. Using the sample thus prepared, each component is quantified by the area percentage of the GPC chromatogram. The peak start and peak end of each component are the minimum values of each peak curve, and the area percentage of the chromatogram can be calculated based on this.
[0074] In addition, the dimer diamine composition has a total area percentage of components (b) and (c) of 4% or less, preferably less than 4%, in a chromatogram obtained by GPC measurement. By keeping the total area percentage of components (b) and (c) at 4% or less, the broadening of the molecular weight distribution of the polyimide can be suppressed.
[0075] The area percentage of the chromatogram of the (b) component is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less. By setting it in such a range, it is possible to suppress the decrease in the molecular weight of the polyimide, and further to widen the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component. It is not necessary for the (b) component to be contained in the dimer diamine composition.
[0076] The area percentage of the chromatogram of component (c) is 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it in such a range, a sudden increase in the molecular weight of the polyimide can be suppressed, and further, an increase in the dielectric tangent of the resin film over a wide frequency range can be suppressed. Note that component (c) does not have to be contained in the dimer diamine composition.
[0077] In addition, when the ratio (b / c) of the area percentages of the chromatograms of the components (b) and (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and less than 1.0. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.
[0078] Furthermore, when the ratio (b / c) of the area percentages of the components (b) and (c) in the chromatograms is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and 1.1 or less. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.
[0079] The dimer diamine composition is available as a commercially available product, and is preferably purified to reduce the amount of components other than the dimer diamine of the component (a), for example, the component (a) is preferably 96% by weight or more. The purification method is not particularly limited, but known methods such as distillation and precipitation purification are suitable. Examples of commercially available products include PRIAMINE 1073 (trade name), PRIAMINE 1074 (trade name), and PRIAMINE 1075 (trade name) manufactured by Croda Japan.
[0080] The adhesive polyimide may contain a diamine residue derived from a diamine component other than the above. Although there is no particular limitation on such a diamine residue, the diamine residue derived from the aromatic diamine exemplified in the description of the thermoplastic polyimide above is preferred.
[0081] The adhesive polyimide preferably has a weight average molecular weight (Mw) in the range of 25,000 to 100,000. By making Mw 25,000 or more, the tear strength and adhesive strength of the film can be improved, and the storage stability of the varnish can be increased. If Mw is less than 25,000, the film becomes brittle, and in a film containing a high concentration of a metal salt of an organic phosphinic acid as a filler component, stress occurs at the interface between the filler and the resin when the film is bent or stretched, which causes breakage or voids at the interface between the filler and the resin. On the other hand, if Mw exceeds 100,000, the viscosity of the varnish increases and the handleability tends to decrease. In addition, the lower the molecular weight of Mw within the above range, the narrower the molecular weight distribution tends to be, so that the more preferred range of Mw is 50,000 to 100,000, and even more preferably 50,000 to 70,000 or less.
[0082] The imide group concentration of the adhesive polyimide is preferably 22% by weight or less, more preferably 20% by weight or less. Here, "imide group concentration" means the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire polyimide structure. If the imide group concentration exceeds 22% by weight, the molecular weight of the resin itself decreases, and the low moisture absorption property deteriorates due to the increase in polar groups, and Tg and elastic modulus increase.
[0083] The adhesive polyimide is most preferably a completely imidized structure. However, a part of the polyimide may be an amic acid. The imidization rate can be determined by measuring the infrared absorption spectrum of the polyimide thin film by a single reflection ATR method using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 It can be calculated from the absorbance of the C=O stretching derived from the imide group.
[0084] (Crosslinking of adhesive polyimide) When the adhesive polyimide has a ketone group, a crosslinking structure can be formed by reacting the ketone group with a crosslinking agent having a functional group that undergoes a nucleophilic reaction. The formation of the crosslinking structure can improve heat resistance. A polyimide having such a crosslinking structure (hereinafter sometimes referred to as "crosslinked polyimide") is an application example of an adhesive polyimide, and is a preferred embodiment. Since the weight average molecular weight varies greatly due to the crosslinking, it is sufficient that the adhesive polyimide before the crosslinking satisfies the above weight average molecular weight.
[0085] As the crosslinking agent, for example, an amino compound having at least two primary amino groups as functional groups (hereinafter, sometimes referred to as "amino compound for crosslinking") is preferably used. A crosslinked structure can be formed by reacting a ketone group of the adhesive polyimide with an amino group of the amino compound for crosslinking to form a C=N bond. In other words, the two primary amino groups in the amino compound function as functional groups that undergo a nucleophilic reaction with the ketone group. The primary amino group is particularly advantageous because it does not involve the generation of a hydroxyl group (-OH) that deteriorates the dielectric properties.
[0086] A preferred tetracarboxylic dianhydride for forming an adhesive polyimide having a ketone group is, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and a preferred diamine compound is, for example, an aromatic diamine such as 4,4'-bis(3-aminophenoxy)benzophenone (BABP) or 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (BABB). For the purpose of forming a crosslinked structure, it is particularly preferred to allow an amino compound for crosslinking to act on the above adhesive polyimide, which contains, with respect to the total tetracarboxylic acid residues, preferably 50 mol % or more, more preferably 60 mol % or more of BTDA residues derived from BTDA. In the present invention, the term "BTDA residue" refers to a tetravalent group derived from BTDA.
[0087] Examples of the amino compound for forming a crosslink include (I) a dihydrazide compound, (II) an aromatic diamine, and (III) an aliphatic amine. Among these, a dihydrazide compound is preferred. Aliphatic amines other than dihydrazide compounds are likely to form a crosslinked structure even at room temperature, which raises concerns about the storage stability of the varnish, while aromatic diamines require high temperatures to form a crosslinked structure. In this way, when a dihydrazide compound is used, it is possible to achieve both the storage stability of the varnish and a shortened curing time. Examples of the dihydrazide compound include oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglyceryl ester dihydrazide, ... Preferred are dihydrazide compounds such as cholic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoedioic acid dihydrazide, 4,4-bisbenzene dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine diacid dihydrazide, itaconic acid dihydrazide, etc. The above dihydrazide compounds may be used alone or in combination of two or more.
[0088] In addition, the above amino compounds, such as (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines, can also be used in combination of two or more kinds beyond categories, such as a combination of (I) and (II), a combination of (I) and (III), or a combination of (I), (II) and (III).
[0089] In addition, from the viewpoint of making the network structure formed by the crosslinking by the crosslinking amino compound denser, the crosslinking amino compound used in the present invention preferably has a molecular weight (weight average molecular weight when the crosslinking amino compound is an oligomer) of 5,000 or less, more preferably 90 to 2,000, and even more preferably 100 to 1,500. Among these, crosslinking amino compounds having a molecular weight of 100 to 1,000 are particularly preferred. When the molecular weight of the crosslinking amino compound is less than 90, only one amino group of the crosslinking amino compound forms a C=N bond with a ketone group of the adhesive polyimide, and the periphery of the remaining amino group becomes three-dimensionally bulky, so that the remaining amino group tends to have difficulty in forming a C=N bond.
[0090] When crosslinking the ketone group in the adhesive polyimide with the crosslinking amino compound, the crosslinking amino compound is added to a resin solution containing the adhesive polyimide to cause a condensation reaction between the ketone group in the adhesive polyimide and the primary amino group of the crosslinking amino compound. This condensation reaction hardens the resin solution to become a hardened product.
[0091] A ketone group in the adhesive polyimide and a functional group of the crosslinking agent are subjected to a nucleophilic reaction to form a crosslink, resulting in a crosslinked polyimide, which is a cured product. The conditions of the nucleophilic reaction for forming the crosslink are not particularly limited and can be selected according to the type of the crosslinking agent. For example, when a primary amino group of an amino compound for forming a crosslink is reacted with a ketone group in the adhesive polyimide, an imine bond (C=N bond) is generated by a condensation reaction by heating, and a crosslinked structure is formed. The conditions of the condensation reaction for forming the crosslink are not particularly limited as long as the ketone group in the adhesive polyimide and the primary amino group of the amino compound for forming the crosslink form an imine bond (C=N bond). The temperature of the heat condensation is preferably within the range of 120 to 220°C, more preferably within the range of 140 to 200°C, for example, in order to release water generated by condensation out of the system, or to simplify the condensation step when a heat condensation reaction is performed subsequently after the synthesis of the adhesive polyimide. The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be determined by measuring the infrared absorption spectrum using, for example, a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1670 cm -1 The decrease or disappearance of the absorption peak due to the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from a nearby imine group.
[0092] The thermal condensation of the ketone group of the adhesive polyimide with the primary amino group of the crosslinking amino compound can be carried out, for example, by the following method: (1) A method in which, following the synthesis (imidization) of adhesive polyimide, an amino compound for crosslinking is added and heated; (2) A method in which an excess amount of an amino compound is charged in advance as a diamine component, and following the synthesis (imidization) of an adhesive polyimide, the remaining amino compound that is not involved in imidization or amidation is used as an amino compound for crosslinking and heated together with the adhesive polyimide; Or, (3) A method in which the adhesive polyimide composition containing the above-mentioned crosslinking amino compound is processed into a predetermined shape (for example, after being applied to a substrate or formed into a film), and then heated; This can be done by, etc.
[0093] In the above description, an example of a crosslinked polyimide having a crosslinked structure formed by the formation of an imine bond has been given in order to impart heat resistance to the adhesive polyimide. However, the present invention is not limited to this example. As a method for curing the polyimide, it is also possible to mix and cure the polyimide with a compound having an unsaturated bond, such as an epoxy resin, an epoxy resin curing agent, maleimide, an activated ester resin, or a resin having a styrene skeleton.
[0094] By using the adhesive polyimide described above, the adhesive layer AD has excellent flexibility and dielectric properties (low dielectric constant and low dielectric tangent). In addition to the metal salt of organic phosphinic acid, the adhesive layer AD may appropriately contain, for example, a plasticizer, a curing resin component such as an epoxy resin, a curing agent, a curing accelerator, an organic or inorganic filler, a coupling agent, and the like.
[0095] <Synthesis of polyimide> The thermoplastic polyimide and non-thermoplastic polyimide constituting the first insulating resin layer 40A and the second insulating resin layer 40B, and the adhesive polyimide constituting the adhesive layer AD can be produced by reacting the above-mentioned tetracarboxylic acid anhydride component and diamine component in a solvent to generate polyamic acid, which is then subjected to heating and ring-closing. For example, the tetracarboxylic acid anhydride component and the diamine component are dissolved in an organic solvent in approximately equal moles, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction, thereby obtaining polyamic acid, which is a precursor of polyimide. In the reaction, the reaction components are dissolved in the organic solvent so that the generated precursor is in the range of 5 to 50% by weight, preferably in the range of 10 to 40% by weight. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of such organic solvents is not particularly limited, but it is preferable to adjust the amount of the organic solvent to be used so that the concentration of the polyamic acid solution obtained by the polymerization reaction is about 5 to 50% by weight.
[0096] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, but it can be concentrated, diluted, or replaced with another organic solvent if necessary. Polyamic acid is generally advantageously used because it has excellent solvent solubility. The viscosity of the polyamic acid solution is preferably within the range of 500 mPa·s to 100,000 mPa·s. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the film during coating using a coater or the like.
[0097] The method for imidizing the polyamic acid to form the adhesive polyimide is not particularly limited, and for example, a heat treatment in which the polyamic acid is heated at a temperature within a range of 80 to 400° C. for 1 to 24 hours is suitably employed.
[0098] [Metal-clad laminate] The metal-clad laminate of the present invention comprises the above-mentioned laminate and a metal layer laminated on one or both sides of the laminate. 3 shows a cross-sectional structure of a metal-clad laminate 200 according to a preferred embodiment of the present invention. The metal-clad laminate 200 has a structure in which a metal layer 110A and a metal layer 110B are laminated on both sides of a laminate 100. Therefore, the metal-clad laminate 200 has a structure in which a metal layer 110A / a first insulating resin layer 40A / an adhesive layer AD / a second insulating resin layer 40B / a metal layer 110B are laminated in this order. The metal layer 110A and the metal layer 110B are located on the outermost sides, respectively, and the first insulating resin layer 40A and the second insulating resin layer 40B are disposed inside them, and further, an adhesive layer AD is disposed between the first insulating resin layer 40A and the second insulating resin layer 40B. A metal-clad laminate 200 having such a layer configuration can also be considered to have a structure in which a first single-sided metal-clad laminate (C1) in which a metal layer 110A, a thermoplastic polyimide layer 10A, a non-thermoplastic polyimide layer 20A, and a thermoplastic polyimide layer 30A are laminated in that order, and a second single-sided metal-clad laminate (C2) in which a metal layer 110B, a thermoplastic polyimide layer 10B, a non-thermoplastic polyimide layer 20B, and a thermoplastic polyimide layer 30B are laminated in that order, are bonded together with an adhesive layer AD so that the insulating resin layer sides face each other.
[0099] 4, a metal-clad laminate 201 may be obtained by using a laminate 101 instead of the laminate 100, and having a structure in which a metal layer 110A and a metal layer 110B are laminated on both sides of the laminate 101. The metal-clad laminate 201 has a structure in which a metal layer 110A, a first insulating resin layer 40A, an adhesive layer AD, a second insulating resin layer 40B, and a metal layer 110B are laminated in this order. In this case, the metal-clad laminate 201 may be considered to have a structure in which a first single-sided metal-clad laminate (C1) in which a metal layer 110A, a thermoplastic polyimide layer 10A, and a non-thermoplastic polyimide layer 20A are laminated in this order, and a second single-sided metal-clad laminate (C2) in which a metal layer 110B, a thermoplastic polyimide layer 10B, and a non-thermoplastic polyimide layer 20B are laminated in this order are bonded together with an adhesive layer AD so that the insulating resin layer sides face each other. Although a double-sided metal-clad laminate having metal layers on both sides of the laminates 100, 101 is shown as an example in Figs. 3 and 4, a single-sided metal-clad laminate having a metal layer on one side of the laminates 100, 101 may also be used.
[0100] (metal layer) The material of the metal layer 110A and the metal layer 110B is not particularly limited, but examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferable. The material of the wiring layer in the circuit board of this embodiment, which will be described later, is the same as that of the metal layer 110A and the metal layer 110B.
[0101] The thickness of the metal layer 110A and the metal layer 110B is not particularly limited, but when a metal foil such as a copper foil is used, the thickness is preferably 35 μm or less, and more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the metal foil is preferably 5 μm. When a copper foil is used, it may be a rolled copper foil or an electrolytic copper foil. In addition, a commercially available copper foil may be used as the copper foil.
[0102] The metal foil may be subjected to a surface treatment using, for example, siding, aluminum alcoholate, aluminum chelate, a silane coupling agent, or the like, for the purpose of, for example, rust prevention or improving adhesive strength.
[0103] [Manufacturing of metal-clad laminates] The metal-clad laminates 200, 201 can be manufactured, for example, by the following method 1 or method 2. The adhesive polyimide that becomes the adhesive layer AD may be crosslinked as described above. [Method 1] First, a first single-sided metal-clad laminate (C1) and a second single-sided metal-clad laminate (C2) having the above-mentioned layer structure are prepared. Next, a solution containing the above-mentioned adhesive polyimide and a filler component is formed into a sheet to form an adhesive film that becomes an adhesive layer AD. This adhesive film is placed between the first insulating resin layer 40A of the first single-sided metal-clad laminate (C1) and the second insulating resin layer 40B of the second single-sided metal-clad laminate (C2), bonded together, and thermocompression bonded. [Method 2] First, a first single-sided metal-clad laminate (C1) and a second single-sided metal-clad laminate (C2) are prepared. Next, an adhesive resin composition that will become an adhesive layer AD is applied to either or both of the first insulating resin layer 40A of the first single-sided metal-clad laminate (C1) and the second insulating resin layer 40B of the second single-sided metal-clad laminate (C2) in a predetermined thickness and dried to form a coating film. Then, the first single-sided metal-clad laminate (C1) and the second single-sided metal-clad laminate (C2) are bonded together on the side of the coating film and thermocompression bonded.
[0104] The first single-sided metal-clad laminate (C1) and the second single-sided metal-clad laminate (C2) used in methods 1 and 2 can be produced, for example, by repeatedly applying and drying a solution of a polyamic acid, which is a precursor of a thermoplastic polyimide or a non-thermoplastic polyimide, onto a metal foil that will become the metal layers 110A and 110B, and then heat-treating it to convert it into an imidization product. The adhesive film used in method 1 can be produced, for example, by applying a solution containing the above-mentioned adhesive polyimide, a filler component, and an organic solvent (sometimes referred to as "adhesive resin composition" in this specification) to a supporting substrate, drying the solution, and then peeling the solution off from the supporting substrate to obtain an adhesive film. The adhesive film and the adhesive resin composition are also preferred embodiments of the present invention. In the above, the method for applying the polyamic acid solution or adhesive resin composition to a metal foil, a supporting substrate, an insulating resin layer, or the like is not particularly limited, and it is possible to apply it using, for example, a coater such as a comma, die, knife, or lip coater.
[0105] The laminates 100, 101 of this embodiment obtained as described above can be used to manufacture circuit boards such as single-sided FPCs or double-sided FPCs by wiring and circuit processing, such as by etching the metal layers 110A and / or metal layers 110B.
[0106] [Adhesive resin composition] Next, the adhesive resin composition according to the embodiment of the present invention will be described. Since the adhesive polyimide is soluble in a solvent, it can be used in the form of a composition containing an organic solvent, and can be preferably used as an adhesive resin composition containing a resin component, a filler component, and an organic solvent. The contents of the resin component and the filler component are as described above. When the adhesive resin composition is formed into a film with a thickness in the range of more than 50 μm and not more than 450 μm, the tensile modulus is in the range of 1.0 GPa to 1.2 GPa, and the storage modulus at 80° C. is in the range of 10 MPa to 20 MPa. This film is the same as the adhesive film described next.
[0107] In the adhesive resin composition, from the viewpoint of ensuring the flame retardancy of the adhesive layer AD and exhibiting a tensile modulus and storage modulus capable of suppressing the occurrence of wrinkles during thermocompression bonding with the insulating resin layer, the weight ratio of the filler component to the total amount of 100 parts by weight of the resin components is in the range of more than 40 parts by weight and not more than 90 parts by weight, preferably more than 40 parts by weight and not more than 80 parts by weight, and more preferably in the range of 45 to 70 parts by weight. If the weight ratio of the filler component is less than 40 parts by weight, not only the flame retardant effect is not fully exhibited, but wrinkles are easily generated during thermocompression bonding with the insulating resin layer, and if it exceeds 90 parts by weight, the elongation when the adhesive layer AD or adhesive film is formed may decrease or the dielectric properties may deteriorate. In addition, from the viewpoint of fully exhibiting the effects of the invention, the total amount of the resin component and the filler component is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight, based on the total solid content in the adhesive resin composition.
[0108] The organic solvent is not particularly limited as long as it can dissolve the adhesive polyimide, and examples thereof include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, cresol, acetone, etc. Two or more of these organic solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination.
[0109] In addition, when an adhesive polyimide having a ketone group in the molecule is used as the resin component, the adhesive resin composition preferably further contains a crosslinking agent having a functional group that undergoes a nucleophilic reaction with the ketone group as an optional component. Here, the adhesive polyimide having a ketone group in the molecule and the crosslinking agent are as described above. The adhesive resin composition preferably contains a crosslinking agent so that the functional group of the crosslinking agent is in the range of 0.04 to 0.50 mol, preferably 0.06 to 0.40 mol, in total, per 1 mol of ketone group contained in the adhesive polyimide. For example, when an amino compound for crosslinking is used as the crosslinking agent, the primary amino group can be in the range of 0.04 to 0.50 mol, preferably 0.06 to 0.40 mol, in total, per 1 mol of ketone group. If the functional group of the crosslinking agent is less than 0.04 mol in total per 1 mol of ketone group, crosslinking does not proceed sufficiently, and heat resistance after curing tends to be difficult to be expressed. On the other hand, if it exceeds 0.5 mol, the dielectric loss tangent tends to increase. This is presumably because the excess crosslinking agent restricts the mobility of the polyimide molecular chains, preventing the formation of an ordered molecular chain structure that is effective in suppressing the dielectric tangent during curing. Also, if the amount of crosslinking agent is too large, the unreacted crosslinking agent acts as a thermoplasticizer, which tends to reduce the heat resistance of the adhesive layer AD.
[0110] The viscosity of the adhesive resin composition is not particularly limited as long as it is a viscosity that allows coating, but for example, it is preferably in the range of 500 mPa·s to 100,000 mPa·s, and more preferably in the range of 1,000 mPa·s to 5,000 mPa·s. If it is out of this range, defects such as uneven thickness and streaks are likely to occur in the adhesive film during the coating operation. In addition, the solid content concentration in the adhesive resin composition is preferably in the range of 30 to 40 wt%, and more preferably in the range of 33 to 37 wt%.
[0111] The adhesive resin composition may appropriately contain optional components such as plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, organic or inorganic fillers other than metal salts of organic phosphinic acids, coupling agents, dispersants, etc., within the scope of the invention.
[0112] The adhesive resin composition can be prepared by the following steps (i) and (ii); (i) mixing a portion of the resin component and a filler component in an organic solvent and stirring to obtain a filler dispersion; And, (ii) a step of mixing the remainder of the resin component with an organic solvent into the filler dispersion and stirring to obtain an adhesive resin composition; The composition can be produced by a method comprising the steps of: In step (i), the weight ratio of the resin content in the filler dispersion is adjusted to within the range of 3 to 15 parts by weight relative to the final total amount of the resin content of 100 parts by weight, and the solid content concentration in the filler dispersion is adjusted to within the range of 40 to 60% by weight. If the weight ratio of the resin content in the filler dispersion obtained in step (i) is less than 3 parts by weight relative to the final total amount of the resin content of 100 parts by weight, or if the solid content concentration exceeds 60% by weight, it becomes difficult to uniformly disperse the filler component, and aggregation occurs. On the other hand, if the weight ratio of the resin content in the filler dispersion obtained in step (i) is more than 15 parts by weight relative to the final total amount of the resin content of 100 parts by weight, or if the solid content concentration is less than 40% by weight, it becomes difficult to blend the filler component at a high concentration of more than 40 parts by weight in step (ii).
[0113] In step (ii), the weight ratio of the filler component in the adhesive resin composition is adjusted to be within the range of more than 40 parts by weight and not more than 90 parts by weight relative to 100 parts by weight of the final total amount of the resin components, and the solid content concentration in the adhesive resin composition is adjusted to be within the range of 30 to 40% by weight. The organic solvent used in steps (i) and (ii) may be the same as the organic solvent described for the adhesive resin composition.
[0114] According to the manufacturing method of the present embodiment, by blending the resin component in multiple stages and adjusting the solid content concentration, it is possible to blend a high concentration of filler component of more than 40 parts by weight per 100 parts by weight of the final total amount of resin components without blending a dispersant and without causing aggregation, and when the adhesive layer AD or adhesive film is formed, both low dielectric tangent and improved flame retardancy are achieved. The adhesive resin composition obtained by the manufacturing method of the present embodiment does not require a dispersant, so it does not need to contain substantially no dispersant. However, it is not prohibited to blend a dispersant to an extent that does not significantly affect the dielectric properties. Note that "substantially does not contain a dispersant" means, for example, an amount less than 1.0 part by weight, preferably an amount of 0.1 part by weight or less, relative to 1.0 part by weight, which is the minimum amount of dispersant required to well disperse 100 parts by weight of the filler component.
[0115] [Adhesive film] Next, the adhesive film according to the embodiment of the present invention will be described. The adhesive film can be produced by applying the adhesive resin composition on any substrate, drying it, and then peeling it off. The adhesive film contains a resin component and a filler component, and the composition of each component is the same as that of the adhesive layer AD. The weight ratio of the filler component to 100 parts by weight of the total amount of the resin components in the adhesive film is in the range of more than 40 parts by weight and not more than 90 parts by weight. In addition, from the viewpoint of fully exhibiting the effects of the invention, the total amount of the resin component and the filler component is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95 to 100% by weight, based on the total solid content in the adhesive film. In addition, the thickness of the adhesive film is preferably the same as that of the adhesive layer AD in the laminate 100, 101, and the tensile modulus of elasticity, storage modulus, dielectric loss tangent under humidity control conditions, and relative dielectric constant of the adhesive film at that time are the same as those of the adhesive layer AD. Furthermore, when a cross section of the adhesive film in the thickness direction is observed under a scanning electron microscope, the total area ratio of filler components having a particle size exceeding 10 μm and filler-dropped parts having a major axis exceeding 10 μm within a surface field of 100 μm × 100 μm is preferably 1% or less, more preferably 0.5% or less, and most preferably 0.1 to 0%, on average within the surface field of any 10 points. In this case, the meanings of "particle size" and "filler-dropped parts" are as explained for the adhesive layer AD.
[0116] [Circuit board] The metal-clad laminates 200 and 201 of the present embodiment are useful mainly as circuit board materials for FPCs, rigid-flex circuit boards, etc. That is, one or both of the two metal layers 110A and 110B of the metal-clad laminates 200 and 201 of the present embodiment are processed into a pattern shape by a conventional method to form a wiring layer, thereby manufacturing a circuit board such as an FPC, which is one embodiment of the present invention.
[0117] [Electronic devices and electronic equipment] The electronic device and electronic equipment of the present embodiment include the circuit board. Examples of the electronic device of the present embodiment include display devices such as liquid crystal displays, organic EL displays, and electronic paper, organic EL lighting, solar cells, touch panels, camera modules, inverters, converters, and components thereof. Examples of the electronic equipment include HDDs, DVDs, mobile phones, smartphones, tablet terminals, electronic control units (ECUs) and power control units (PCUs) for automobiles. In these electronic devices and electronic equipment, the circuit board is preferably used as a component such as wiring for movable parts, cables, and connectors. EXAMPLES
[0118] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, various measurements and evaluations were performed according to the following methods, unless otherwise specified.
[0119] [Viscosity measurement] The viscosity was measured at 25° C. using an E-type viscometer (manufactured by Brookfield, product name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the value was read when the viscosity stabilized 2 minutes after the start of the measurement.
[0120] [Measurement of weight average molecular weight (Mw)] The weight average molecular weight was measured by gel permeation chromatography (manufactured by Tosoh Corporation, product name: HLC-8220GPC was used). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.
[0121] [Measurement of dielectric constant (Dk) and dielectric loss tangent (Df)] Using a vector network analyzer (Agilent, product name E8363C) and an SPDR resonator, the relative permittivity and dielectric loss tangent of the resin sheet at 10 GHz were measured under conditions of "humidity conditioning" and "water absorption." "Humidity conditioning" refers to leaving the sheet for 24 hours under conditions of temperature: 24-26°C and humidity: 45°C-55%RH, while "water absorption" refers to immersion in pure water for 48 hours, followed by measurements under conditions of temperature: 24-26°C and humidity: 45°C-55%RH.
[0122] [Measurement of coefficient of thermal expansion (CTE)] The adhesive layer sheet peeled off from the single-sided metal-clad laminate or release substrate was cut into a size of 3 mm x 20 mm, and was heated from 5°C to 50°C at a constant heating rate while applying a load of 5.0 g using a thermomechanical analyzer (manufactured by Hitachi High-Tech Science Corporation, product name: TMA7100), and the average thermal expansion coefficient (thermal expansion coefficient) from 10°C to 20°C was obtained. In addition, the polyimide film was cut into a similar size, heated from 30°C to 265°C at a constant heating rate while applying a load of 5.0 g, and further held at that temperature for 10 minutes, and then cooled at a rate of 5°C / min, and the average thermal expansion coefficient (thermal expansion coefficient) from 250°C to 100°C was obtained.
[0123] [Measurement of storage modulus and glass transition temperature (Tg)] The storage modulus was measured by cutting the adhesive layer sheet peeled from the single-sided metal-clad laminate or release substrate to a size of 5 mm x 20 mm, heating it stepwise from 30 ° C to 100 ° C at a heating rate of 4 ° C / min using a dynamic viscoelasticity device (DMA: manufactured by TA Instruments, product name: RSA-G2) and measuring it at a frequency of 6 Hz, and measuring the storage modulus at the lamination temperature of 80 ° C. In addition, the polyimide film was cut to a similar size, heated stepwise from 30 ° C to 400 ° C at a heating rate of 4 ° C / min, and measuring it at a frequency of 11 Hz, and the maximum temperature at which the value of Tan δ during the measurement was maximum was defined as Tg. In addition, the storage modulus at 30 ° C was 1.0 × 10 8 Pa or more, and the storage modulus at 300°C is 3.0×10 7Polyimides with a storage modulus of less than 1.0 × 10 Pa at 30°C are judged to be "thermoplastic." 9 Pa or more, and the storage modulus at 300°C is 3.0×10 8 Polyimides with a thermal expansion coefficient of 100 Pa or more were judged to be "non-thermoplastic".
[0124] [Measurement of tensile strength, tensile elongation and tensile modulus] Using a Strograph R-1 manufactured by Toyo Seiki Seisakusho, the tensile strength, tensile elongation and tensile modulus were measured under an environment of 23°C and 50% relative humidity. The measurement samples were cut into a size of MD; 250 mm × TD; 12.7 mm from a single-sided metal-clad laminate or an adhesive layer sheet peeled from a release substrate, and measured under the conditions of load cell; 500 N, tensile speed; 50 mm / min, and chuck distance; 50 mm. The tensile strength was the stress value calculated by dividing the load at the time of sample breakage by the cross-sectional area, and the tensile elongation was the value obtained by dividing the strain at the time of sample breakage by the length of the sample in the MD direction. The tensile modulus was calculated by the least squares method from the strain range of 0.05% to 0.5%.
[0125] [Measurement of particle size of filler used] Using a laser diffraction particle size analyzer (Malvern Instruments, trade name: Master Sizer 3000), particle size was measured by a laser diffraction / scattering measurement method under conditions of 2-propanol as a dispersion medium and a particle refractive index of 1.50.
[0126] [Flame retardancy evaluation] Flame retardancy was measured by the following procedure. The copper foil of the metal-clad laminate was etched away using an aqueous solution of ferric chloride to obtain a film, which was used as a flame retardancy evaluation sample (width 50 mm x length 180 mm). This flame retardancy evaluation sample was measured for the burning time (t1) after the first flame separation in accordance with the thin material vertical test method of the UL94VTM test. In addition, if the probability of the burning time (t1) of 10 samples being less than 10 seconds was more than 80%, it was evaluated as ◯ (pass), and if it was 80% or less, it was evaluated as × (fail).
[0127] [Evaluation of thickness unevenness] The thickness unevenness was measured by the following procedure. The adhesive layer sheet peeled off from the single-sided metal-clad laminate or release substrate was measured in 1 mm increments in the TD direction using a contact-type digital thickness gauge (Nikon DIGIMICRO MH-15), and the average thickness of the portion excluding the end 30 mm was calculated. The absolute values of the differences between the thickness at each measurement point excluding the end 30 mm and the average thickness were summed up, and the sum was divided by the number of measurement points to determine the thickness unevenness.
[0128] [Evaluation of wrinkles and adhesion] The evaluation of wrinkles was performed by visually observing the double-sided copper-clad laminate after lamination to confirm the presence or absence of step-like wrinkles due to deformation or folding of the adhesive layer sheet. In addition, the single-sided copper-clad laminate was peeled off from the double-sided copper-clad laminate after lamination, and the surface of the adhesive layer sheet was visually observed to confirm the presence or absence of color change due to deformation or folding of the adhesive layer sheet.
[0129] [Evaluation of filler shedding and evaluation of coarse particle ratio] To evaluate the filler shedding properties, samples were cut from the adhesive layer sheet to a size of 10 mm in MD x 2 mm in TD, and cut in the thickness direction from above at 90 degrees to the plane of the sample using a small slicer (HW-1, manufactured by Jusco Engineering) equipped with a single-edged razor (FAS-10, manufactured by Feather Safety Razor Co., Ltd.). The cut surface was then observed with a scanning electron microscope (S-4700, manufactured by Hitachi, Ltd.) at an accelerating voltage of 5.0 kV to confirm the presence or absence of voids in the cross section of the adhesive layer. In addition, in observing a cut surface of the sample in the thickness direction using the above-mentioned scanning electron microscope (Hitachi, S-4700), the total area ratio of coarse filler particles with a particle diameter exceeding 10 μm and fallen filler parts with a major axis exceeding 10 μm within a surface field of 100 μm × 100 μm was measured, and the coarse particle ratio was calculated by finding the average value of the surface field of any 10 points.
[0130] The abbreviations used in the examples represent the following compounds. BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride PMDA: Pyromellitic dianhydride m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane TPE-R: 1,3-bis(4-aminophenoxy)benzene BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride DDA: aliphatic diamine having 36 carbon atoms [manufactured by Croda Japan Co., Ltd., product name: PRIAMINE 1074, distilled and purified, amine value: 210 mg KOH / g, mixture of dimer diamines having cyclic and chain structures, component (a): 97.9%, component (b): 0.3%, component (c): 1.8%] The "%" for component (a), component (b), and component (c) refer to the area percentage of the chromatogram in the GPC measurement. The molecular weight of DDA was calculated using the following formula. Molecular weight = 56.1 x 2 x 1000 / amine value NMP: N-methyl-2-pyrrolidone DMAc: N,N-dimethylacetamide N-12: Dodecanedioic acid dihydrazide OP945: organic phosphinic acid aluminum salt (manufactured by Clariant Japan, trade name: Exolit OP945, D 50 ;2.1μm, D 95 3.0 μm, maximum particle size: 6.7 μm, percentage of particles with a size exceeding 10 μm: 0% by volume OP935: organic phosphinic acid aluminum salt (manufactured by Clariant Japan, trade name: Exolit OP935, D 50 ;2.7μm, D 95 6.8 μm, maximum particle size: 11.5 μm, percentage of particles with a diameter of more than 10 μm: 1.07% by volume
[0131] (Synthesis Example 1) <Preparation of resin solution for adhesive layer> Under a nitrogen stream, a polyamic acid solution was prepared by charging a reaction vessel with 45.43 parts by weight of BTDA (0.1410 parts by mole), 74.57 parts by weight of DDA (0.1396 parts by mole), 168 parts by weight of NMP, and 112 parts by weight of xylene, and mixing thoroughly for 1 hour at 40° C. The polyamic acid solution was heated to 190° C., heated and stirred for 5 hours, and 98 parts by weight of xylene was added to complete the imidization, preparing polyimide solution 1 (solid content: 30% by weight, weight average molecular weight: 52,800).
[0132] (Synthesis Example 2) <Preparation of polyamic acid solution for insulating resin layer> Under a nitrogen stream, 78.36 parts by weight of m-TB (0.3691 mol parts), 7.97 parts by weight of BAPP (0.0194 mol parts), and DMAc in an amount that would result in a solids concentration of 15% by weight after polymerization were added to the reaction vessel and stirred at room temperature to dissolve. Next, 50.10 parts by weight of PMDA (0.2297 mol parts) and 45.05 parts by weight of BPDA (0.1531 mol parts) were added, and the polymerization reaction was continued by stirring at room temperature for 3 hours to prepare polyamic acid solution 1 (viscosity: 28,900 mPa s). The storage modulus of the polyimide film obtained by applying polyamic acid solution 1 to a substrate and drying it to imidize it was measured and found to be "non-thermoplastic."
[0133] (Synthesis Example 3) <Preparation of polyamic acid solution for insulating resin layer> Polyamic acid solution 2 (viscosity: 2,650 mPa s) was prepared in the same manner as in Synthesis Example 2, except that 3.48 parts by weight of m-TB (0.0164 mol parts), 27.14 parts by weight of TPE-R (0.0928 mol parts), DMAc in an amount such that the solid concentration after polymerization was 12% by weight, and 9.72 parts by weight of PMDA (0.0446 mol parts) and 19.66 parts by weight of BPDA (0.0668 mol parts) were used as the raw material composition. Polyamic acid solution 2 was applied to a substrate, dried, and imidized to obtain a polyimide film, and the storage modulus was measured, resulting in a value of "thermoplastic."
[0134] <Preparation of Resin Varnish for Adhesive Layer> (Combination example 1) 9.47 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, and 131.11 parts by weight of OP945 (48.28 parts by weight for a total of 100 parts by weight of the final resin content), 120.33 parts by weight of xylene, and 21.00 parts by weight of NMP were added to dilute and stir using a planetary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 19.33 parts by weight of xylene were added and stirred for 2 hours to prepare adhesive composition 1 (viscosity: 2,910 mPa s).
[0135] (Combination example 2) 9.47 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, and 157.33 parts by weight of OP945 (57.94 parts by weight for a total of 100 parts by weight of the final resin content), 128.67 parts by weight of xylene, and 22.00 parts by weight of NMP were added to dilute and stir using a planetary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 16.67 parts by weight of xylene were added and stirred for 2 hours to prepare adhesive composition 2 (viscosity: 3,150 mPa s).
[0136] (Combination example 3) 9.47 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, and 183.56 parts by weight of OP945 (67.59 parts by weight for a total of 100 parts by weight of the final resin content), 137.00 parts by weight of xylene, and 23.00 parts by weight of NMP were added to dilute and stir using a planetary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 15.00 parts by weight of xylene were added and stirred for 2 hours to prepare adhesive composition 3 (viscosity: 3,320 mPa s).
[0137] (Combination example 4) 9.47 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, diluted with 65.56 parts by weight of OP945 (24.14 parts by weight for a total of 100 parts by weight of the final resin content), 95.33 parts by weight of xylene, and 18.33 parts by weight of NMP, and stirred with a planetary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 26.67 parts by weight of xylene were added and stirred for 2 hours to prepare adhesive composition 4 (viscosity: 2,230 mPa s).
[0138] (Combination example 5) 9.47 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, and 91.78 parts by weight of OP945 (33.80 parts by weight for a total of 100 parts by weight of the final resin content), 103.67 parts by weight of xylene, and 19.00 parts by weight of NMP were added to dilute and stir using a planetary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 24.00 parts by weight of xylene were added and stirred for 2 hours to prepare adhesive composition 5 (viscosity: 2,450 mPa s).
[0139] (Combination example 6) 9.47 parts by weight of N-12 was mixed with 100.00 parts by weight of polyimide solution 1, diluted with 104.89 parts by weight of OP945 (38.62 parts by weight for a total of 100 parts by weight of the final resin content), 112.00 parts by weight of xylene, and 20.00 parts by weight of NMP, and stirred with a planetary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 21.67 parts by weight of xylene were added and stirred for 2 hours to prepare adhesive composition 6 (viscosity: 2,690 mPa s).
[0140] (Combination example 7) 873.67 parts by weight of polyimide solution 1 was diluted with 145.33 parts by weight of xylene and 22.00 parts by weight of NMP, and 9.47 parts by weight of N-12 and 157.33 parts by weight of OP935 (57.94 parts by weight for a total of 100 parts by weight of the final resin content) were added and stirred for 2 hours to prepare adhesive composition 7 (viscosity: 3,030 mPa s).
[0141] (Example 1) <Preparation of single-sided metal-clad laminate 1> On a long copper foil 1 (electrolytic copper foil, thickness: 12 μm, surface roughness Rz of the resin layer side: 0.6 μm, width: 0.5 m), a polyamic acid solution 2 was uniformly applied using a comma coater so that the thickness after curing would be about 2 to 3 μm, and then the solution was heated and dried at 145 ° C to remove the solvent. Next, the polyamic acid solution 1 was uniformly applied thereon so that the thickness after curing would be about 14 to 16 μm, and the solution was heated and dried at 80 to 145 ° C to remove the solvent. Further, the polyamic acid solution 2 was uniformly applied thereon so that the thickness after curing would be about 2 to 3 μm, and then the solution was heated and dried at 145 ° C to remove the solvent. Further, a stepwise heat treatment was performed from 120 ° C to 360 ° C to complete the imidization, and a long single-sided metal-clad laminate 1 with a polyimide layer thickness of 20 μm was prepared.
[0142] <Preparation of Polyimide Film 1> The copper foil layer of the single-sided metal-clad laminate 1 was etched away using an aqueous solution of ferric chloride to prepare a polyimide film 1 having a thickness of 20 μm. The CTE was 20 ppm / K, the Dk and Df of the humidified laminate were 3.40 and 0.0033, respectively, and the Dk and Df of the humidified laminate were 3.40 and 0.0070, respectively. The Tg was 290°C, and the storage moduli at 30°C and 125°C were 8.9×10 9 Pa, 5.9×10 9 It was Pa.
[0143] [Example 1] Using a die coater, the adhesive composition 1 prepared in Formulation Example 1 was continuously and uniformly applied to the insulating resin layer side of the long single-sided metal-clad laminate 1 so that the thickness after drying was 60 μm, and then the adhesive composition 1 was heated and dried stepwise from 80 ° C. to 160 ° C. to remove the solvent, and a single-sided metal-clad laminate 1a' with an adhesive layer was obtained. In addition, the adhesive layer was peeled off from the single-sided metal-clad laminate 1a' with an adhesive layer to obtain an adhesive layer sheet 1. The adhesive layer sheet 1 had a tensile modulus of 1.07 GPa, a tensile elongation of 183%, a tensile strength of 24 MPa, a storage modulus at 80 ° C. of 12.1 MPa, a CTE of 111 ppm / K, Dk and Df at humidity control of 2.70 and 0.0023, respectively, and a thickness unevenness of 0.77 μm. In addition, in the evaluation of the filler shedding property, there were no voids in the adhesive layer cross section, and no shedding of OP945 was confirmed. Furthermore, no filler components with particle sizes exceeding 10 μm and no filler-dropped parts with major axes exceeding 10 μm were found within a surface field of 100 μm×100 μm, even when observing any 10 points within the surface field.
[0144] Next, the adhesive layer side of the single-sided metal-clad laminate 1a' with adhesive layer was placed in contact with the insulating resin layer side of the other single-sided metal-clad laminate 1, and these were continuously stacked and thermocompressed while being transported via guide rolls using a heating and pressing device having at least one pair of metallic heating and pressing rolls (roll surface temperature: 80°C) and a roll covered with silicone rubber, to obtain a double-sided copper-clad laminate 1. The double-sided copper-clad laminate 1 had no wrinkles and good overall adhesion.
[0145] [Example 2] A single-sided metal-clad laminate 2a' with an adhesive layer was obtained in the same manner as in Example 1, except that the adhesive composition 2 was used. The adhesive layer was peeled off from the single-sided metal-clad laminate 2a' with an adhesive layer to obtain an adhesive layer sheet 2. The adhesive layer sheet 2 had a tensile modulus of 1.03 GPa, a tensile elongation of 165%, a tensile strength of 20 MPa, a storage modulus of 14.1 MPa at 80 ° C., a CTE of 103 ppm / K, Dk and Df at humidity control of 2.70 and 0.0025, respectively, and a thickness unevenness of 0.65 μm. In addition, in the evaluation of the filler falling off property, there were no voids in the cross section of the adhesive layer, and no falling off of OP945 was confirmed. Furthermore, no filler components with a particle diameter exceeding 10 μm and no filler falling off parts with a major axis exceeding 10 μm were confirmed even when observing the surface field of any 10 points.
[0146] Next, a double-sided copper-clad laminate 2 was obtained in the same manner as in Example 1, except that an adhesive layer-attached single-sided metal-clad laminate 2a' was used. The double-sided copper-clad laminate 2 had no wrinkles and good overall adhesion.
[0147] [Example 3] A single-sided metal-clad laminate 3a' with an adhesive layer was obtained in the same manner as in Example 1, except that the adhesive composition 3 was used. The adhesive layer was peeled off from the single-sided metal-clad laminate 3a' with an adhesive layer to obtain an adhesive layer sheet 3. The adhesive layer sheet 3 had a tensile modulus of 1.09 GPa, a tensile elongation of 176%, a tensile strength of 19 MPa, a storage modulus of 17.4 MPa at 80 ° C., a CTE of 98 ppm / K, Dk and Df at humidity control of 2.70 and 0.0025, respectively, and a thickness unevenness of 0.61 μm. In addition, in the evaluation of the filler falling off property, there were no voids in the cross section of the adhesive layer, and no falling off of OP945 was confirmed. Furthermore, no filler components with a particle diameter exceeding 10 μm and no filler falling off parts with a major axis exceeding 10 μm were confirmed even when observing the surface field of any 10 points.
[0148] Next, a double-sided copper-clad laminate 3 was obtained in the same manner as in Example 1, except that an adhesive layer-attached single-sided metal-clad laminate 3a' was used. The double-sided copper-clad laminate 3 had no wrinkles and good overall adhesion.
[0149] [Example 4] A single-sided metal-clad laminate 4a' with an adhesive layer was obtained in the same manner as in Example 2, except that the thickness after drying was set to 75 μm. The adhesive layer was peeled off from the single-sided metal-clad laminate 4a' with an adhesive layer to obtain an adhesive layer sheet 4. The adhesive layer sheet 4 had a tensile modulus of 1.04 GPa, a tensile elongation of 166%, a tensile strength of 21 MPa, a storage modulus of 14.3 MPa at 80 ° C., a CTE of 105 ppm / K, Dk and Df at humidity control of 2.70 and 0.0025, respectively, and a thickness unevenness of 1.22 μm. In addition, in the evaluation of the filler falling off property, there were no voids in the cross section of the adhesive layer, and no falling off of OP945 was confirmed. Furthermore, no filler components with a particle diameter exceeding 10 μm and no filler falling off parts with a major axis exceeding 10 μm were confirmed even when observing the surface field of any 10 points.
[0150] Next, a double-sided copper-clad laminate 4 was obtained in the same manner as in Example 1, except that an adhesive layer-attached single-sided metal-clad laminate 4a' was used. The double-sided copper-clad laminate 4 had no wrinkles and good overall adhesion.
[0151] Comparative Example 1 A single-sided metal-clad laminate 5a' with an adhesive layer was obtained in the same manner as in Example 1, except that the adhesive composition 4 was used. The adhesive layer was peeled off from the single-sided metal-clad laminate 5a' with an adhesive layer to obtain an adhesive layer sheet 5. The adhesive layer sheet 5 had a tensile modulus of 0.87 GPa, a tensile elongation of 207%, a tensile strength of 31 MPa, a storage modulus of 6.1 MPa at 80 ° C., a CTE of 122 ppm / K, Dk and Df at humidity control of 2.70 and 0.0022, respectively, and a thickness unevenness of 1.05 μm. In addition, in the evaluation of the filler falling off property, there were no voids in the cross section of the adhesive layer, and no falling off of OP945 was confirmed. Furthermore, no filler components with a particle diameter exceeding 10 μm and no filler falling off parts with a major axis exceeding 10 μm were confirmed even when observing the surface field of any 10 points.
[0152] Next, a double-sided copper-clad laminate 5 was obtained in the same manner as in Example 1, except that an adhesive layer-attached single-sided metal-clad laminate 5a' was used. Wrinkles were generated in the double-sided copper-clad laminate 5, and poor adhesion occurred due to the wrinkles.
[0153] Comparative Example 2 A single-sided metal-clad laminate 6a' with an adhesive layer was obtained in the same manner as in Example 1, except that the adhesive composition 5 was used. The adhesive layer was peeled off from the single-sided metal-clad laminate 6a' with an adhesive layer to obtain an adhesive layer sheet 6. The adhesive layer sheet 6 had a tensile modulus of 0.93 GPa, a tensile elongation of 199%, a tensile strength of 27 MPa, a storage modulus of 80 ° C. of 8.4 MPa, a CTE of 118 ppm / K, Dk and Df at humidity control of 2.70 and 0.0022, respectively, and a thickness unevenness of 0.99 μm. In addition, in the evaluation of the filler falling off property, there were no voids in the cross section of the adhesive layer, and no falling off of OP945 was confirmed. Furthermore, no filler components with a particle diameter exceeding 10 μm and no filler falling off parts with a major axis exceeding 10 μm were confirmed even when observing the surface field of any 10 points.
[0154] Next, a double-sided copper-clad laminate 6 was obtained in the same manner as in Example 1, except that an adhesive layer-attached single-sided metal-clad laminate 6a' was used. Wrinkles were generated in the double-sided copper-clad laminate 6, and poor adhesion occurred due to the wrinkles.
[0155] Comparative Example 3 A single-sided metal-clad laminate 7a' with an adhesive layer was obtained in the same manner as in Example 1, except that the adhesive composition 6 was used. The adhesive layer was peeled off from the single-sided metal-clad laminate 7a' with an adhesive layer to obtain an adhesive layer sheet 7. The adhesive layer sheet 7 had a tensile modulus of 0.97 GPa, a tensile elongation of 192%, a tensile strength of 26 MPa, a storage modulus of 9.7 MPa at 80 ° C., a CTE of 112 ppm / K, Dk and Df at humidity control of 2.70 and 0.0023, respectively, and a thickness unevenness of 0.85 μm. In addition, in the evaluation of the filler falling off property, there were no voids in the cross section of the adhesive layer, and no falling off of OP945 was confirmed. Furthermore, no filler components with a particle diameter exceeding 10 μm and no filler falling off parts with a major axis exceeding 10 μm were confirmed even when observing the surface field of any 10 points.
[0156] Next, a double-sided copper-clad laminate 7 was obtained in the same manner as in Example 1, except that an adhesive layer-attached single-sided metal-clad laminate 7a' was used. Slight wrinkles were generated in the double-sided copper-clad laminate 7, and poor adhesion occurred due to the wrinkles.
[0157] Comparative Example 4 A single-sided metal-clad laminate 8a' with an adhesive layer was obtained in the same manner as in Example 4, except that the adhesive composition 4 was used. The adhesive layer was peeled off from the single-sided metal-clad laminate 8a' with an adhesive layer to obtain an adhesive layer sheet 8. The adhesive layer sheet 8 had a tensile modulus of 0.91 GPa, a tensile elongation of 205%, a tensile strength of 30 MPa, a storage modulus of 5.9 MPa at 80 ° C., a CTE of 120 ppm / K, Dk and Df at humidity control of 2.70 and 0.0022, respectively, and a thickness unevenness of 1.50 μm. In addition, in the evaluation of the filler falling off property, there were no voids in the cross section of the adhesive layer, and no falling off of OP945 was confirmed. Furthermore, no filler components with a particle diameter exceeding 10 μm and no filler falling off parts with a major axis exceeding 10 μm were confirmed even when observing the surface field of any 10 points.
[0158] Next, a double-sided copper-clad laminate 8 was obtained in the same manner as in Example 1, except that an adhesive layer-attached single-sided metal-clad laminate 8a' was formed. Wrinkles were generated in the double-sided copper-clad laminate 8, and poor adhesion occurred due to the wrinkles.
[0159] [Example 5] The adhesive composition 2 was applied to one side of a long release PET film 1 (manufactured by Higashiyama Film Co., Ltd., product name: HY-S05, thickness: 25 μm) so that the thickness after drying was 60 μm, and the film was heated and dried stepwise from 80 ° C to 160 ° C to remove the solvent, and the adhesive layer was peeled off from the release PET film 1 to obtain an adhesive layer sheet 9 having a thickness of 60 μm. The tensile modulus of the adhesive layer sheet 9 was 1.05 GPa, the storage modulus at 80 ° C was 13.9 MPa, the tensile elongation was 163%, the tensile strength was 20 MPa, the CTE was 100 ppm / K, the Dk and Df at the time of humidity control were 2.70 and 0.0025, respectively, and the thickness unevenness was 0.67 μm. In addition, in the evaluation of the filler falling off property, as shown in FIG. 5, there was no void in the adhesive layer cross section, and no falling off of OP945 was confirmed. Furthermore, no filler components with particle sizes exceeding 10 μm and no filler-dropped parts with major axes exceeding 10 μm were found within a surface field of 100 μm×100 μm, even when observing any 10 points within the surface field.
[0160] Two long single-sided metal-clad laminates 1 were arranged so that the insulating resin layer faces of the two sheets were in contact with both sides of the adhesive layer sheet 9, and these sheets were continuously superimposed and thermocompressed while being transported via a guide roll using a heating and pressing device having at least one pair of a metallic heating and pressing roll (roll surface temperature: 80°C) and a roll covered with silicone rubber, to obtain a double-sided copper-clad laminate 9. The double-sided copper-clad laminate 9 had no wrinkles and good overall adhesion.
[0161] Comparative Example 5 A single-sided metal-clad laminate 10a' with an adhesive layer was obtained in the same manner as in Example 1, except that the adhesive composition 7 was used. The adhesive layer was peeled off from the single-sided metal-clad laminate 10a' with an adhesive layer to obtain an adhesive layer sheet 10. The adhesive layer sheet 10 had a tensile modulus of 1.05 GPa, a tensile elongation of 162%, a tensile strength of 19 MPa, a storage modulus of 14.2 MPa at 80 ° C., a CTE of 102 ppm / K, Dk and Df of 2.70 and 0.0025, respectively, and a thickness unevenness of 0.68 μm. In addition, in the evaluation of the filler dropout property, as shown in FIG. 6, filler components with a particle diameter of 10 μm or more and voids in the adhesive layer cross section (filler dropout parts with a major axis exceeding 10 μm) were observed, and a state in which coarse particles in OP935 had fallen off was observed.
[0162] As described above, the adhesive layer sheets 1 to 4 and 9 shown in the examples have an increased tensile modulus and storage modulus at 80°C due to the incorporation of OP945 at a high concentration, and deformation due to shear stress during lamination of a single-sided metal-clad laminate is less likely to occur, and wrinkles due to such deformation are suppressed. In addition, it is believed that the incorporation of OP945 at a high concentration facilitates friction between inorganic particles in the adhesive composition, suppressing fluidity at high temperatures, thereby reducing thickness unevenness. In addition, in Comparative Example 5, when a resin composition containing a high concentration of OP935 with a maximum particle size of 10 μm or more is incorporated by the conventional incorporation method of directly incorporating a filler into a diluted resin varnish, and an adhesive layer sheet is produced, the particle size in the adhesive layer sheet is large, and it is believed that the filler is easily removed by shear stress due to cutting. Therefore, in the form of this comparative example, there is a concern that the filler may fall off during cutting, resulting in the generation of foreign matter during the process, or the filler may fall off during drilling, leading to poor through-hole plating.
[0163] <Preparation of Laminated Films 1 to 9> The double-sided copper-clad laminates 1 to 9 were slit and cut to a specified size, then placed in a thermostatic chamber and heat-treated at 180°C for 24 hours. The copper foil layer was then etched away using an aqueous ferric chloride solution to prepare laminate films 1 to 9 with thicknesses of 100 to 125 μm.
[0164] The dielectric properties of the adhesive layer sheets 1 to 9 and the dielectric properties and flame retardancy evaluation results of the laminated films 1 to 9 are shown in Table 1.
[0165] [Table 1]
[0166] Although the Df of the adhesive layer sheet during humidity conditioning tended to increase as OP945 increased, the Df of the laminated films 1 to 9 showed similar values. In addition, the Df of the adhesive layer sheet during water absorption tended to increase more significantly than during humidity conditioning as OP945 increased. On the other hand, in Examples 1 to 5, the Df of the laminated film during water absorption was lower than the estimated Df calculated from the Df of the polyimide film 1 and the adhesive layer sheet during water absorption, taking into account the thickness ratio. Even if the Df of the adhesive layer sheet during water absorption deteriorates, it is considered that this is the result of suppressing water absorption of the adhesive layer sheet by having the polyimide film 1 laminated on both sides.
[0167] The estimated Df value of the laminated film when absorbing water was calculated based on the following formula (1).
[0168]
number
[0169] Regarding flame retardancy, the probability that the combustion time (t1) of 10 samples was less than 10 seconds exceeded 80% for the laminate films 1 to 4 and 9 shown in the examples, and they were rated as "good," while the probability was less than 80% for the laminate films 5 to 8 shown in the comparative examples, and they were rated as "bad."
[0170] As described above in detail, the laminates and metal-clad laminates according to the embodiments of the present invention have excellent dielectric properties, flame retardancy and processability, and are thought to be designed to suppress uneven thickness and wrinkles during lamination.
[0171] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible. [Explanation of symbols]
[0172] Reference Signs List 10A, 10B...thermoplastic polyimide layers, 20A, 20B...non-thermoplastic polyimide layers, 30A, 30B...thermoplastic polyimide layers, 40A...first insulating resin layer, 40B...second insulating resin layer, 100, 101...laminate, 110A, 110B...metal layers, 200, 201...metal-clad laminate, AD...adhesive layer
Claims
1. A first insulating resin layer; A second insulating resin layer; an adhesive layer laminated between the first insulating resin layer and the second insulating resin layer so as to be in contact with the first insulating resin layer and the second insulating resin layer; A laminate comprising: a total thickness T1 of the first insulating resin layer, the adhesive layer, and the second insulating resin layer is within a range of 70 to 500 μm, a thickness T2 of the adhesive layer is within a range of more than 50 μm and not more than 450 μm, and a ratio (T2 / T1) of T2 to T1 is within a range of more than 0.5 and not more than 0.96, The adhesive layer contains a resin component and a filler component, the resin component contains a polyimide having tetracarboxylic acid residues derived from a tetracarboxylic acid anhydride component and diamine residues derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues; A laminate characterized in that the filler component contains a metal salt of an organic phosphinic acid, and the weight ratio of the filler component to 100 parts by weight of a total amount of the resin components is in the range of more than 40 parts by weight and not more than 90 parts by weight.
2. 2. A laminate as described in claim 1, wherein, when a thickness direction cross section of the adhesive layer is observed under a scanning electron microscope, within a surface field of 100 μm x 100 μm, the total area ratio of filler components having a particle diameter exceeding 10 μm and filler detached parts having a major axis exceeding 10 μm is 1% or less on average over any 10 points of the surface field.
3. 2. The laminate according to claim 1, wherein the polyimide has a ketone group in the molecule, and the resin component contains a crosslinking agent having a functional group which undergoes a nucleophilic reaction with the ketone group.
4. 2. The laminate according to claim 1, wherein the polyimide has a ketone group in the molecule and forms a crosslinked structure by a reaction with a crosslinking agent having a functional group which undergoes a nucleophilic reaction with the ketone group.
5. The laminate according to claim 1 , wherein the adhesive layer has a tensile modulus of elasticity in the range of 1.0 GPa or more and 1.2 GPa or less.
6. The laminate according to claim 1 , wherein the adhesive layer has a storage modulus at 80° C. in the range of 10 MPa or more and 20 MPa or less.
7. 2. The laminate according to claim 1, wherein the first insulating resin layer and the second insulating resin layer are multi-layer polyimide layers having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer.
8. 8. The laminate according to claim 7, wherein the multi-layer polyimide layer has an outermost layer which is a thermoplastic polyimide layer.
9. 2. The laminate according to claim 1, wherein the length in the width direction (TD direction) is in the range of 0.2 m to 2.0 m, and the laminate is long.
10. A metal-clad laminate comprising the laminate according to claim 1 and a metal layer laminated on one or both sides of the laminate.
11. A circuit board comprising the laminate according to claim 1 and a wiring layer laminated on one or both sides of the laminate.
12. An electronic device comprising the circuit board according to claim 11.
13. An electronic device comprising the circuit board according to claim 11.
14. An adhesive resin composition comprising a resin component, a filler component, and an organic solvent, the resin component contains a polyimide having tetracarboxylic acid residues derived from a tetracarboxylic acid anhydride component and diamine residues derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues; The filler component contains a metal salt of an organic phosphinic acid, The weight ratio of the filler component to the total amount of the resin components (100 parts by weight) is in the range of more than 40 parts by weight and not more than 90 parts by weight, An adhesive resin composition having a tensile modulus of 1.0 GPa or more and 1.2 GPa or less when formed into a film with a thickness of more than 50 μm and not more than 450 μm, and a storage modulus at 80° C. of 10 MPa or more and 20 MPa or less.
15. A method for producing the adhesive resin composition according to claim 14, comprising the steps of: (i) and (ii); (i) mixing and stirring a portion of the resin component and the filler component in an organic solvent to obtain a filler dispersion; and (ii) a step of mixing the remainder of the resin component with an organic solvent into the filler dispersion and stirring the mixture to obtain the adhesive resin composition; Including, A method for producing an adhesive resin composition, characterized in that in step (i), the weight ratio of the resin content in the filler dispersion is within the range of 3 to 15 parts by weight relative to 100 parts by weight of a final total amount of the resin content, and the solid content concentration in the filler dispersion is adjusted to be within the range of 40 to 60 parts by weight, and in step (ii), the weight ratio of the filler component in the adhesive resin composition is within the range of more than 40 parts by weight and not more than 90 parts by weight relative to 100 parts by weight of a final total amount of the resin content.
16. An adhesive film containing a resin component and a filler component, the resin component contains a polyimide having tetracarboxylic acid residues derived from a tetracarboxylic acid anhydride component and diamine residues derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues; The filler component contains a metal salt of an organic phosphinic acid, The weight ratio of the filler component to the total amount of the resin components (100 parts by weight) is in the range of more than 40 parts by weight and not more than 90 parts by weight, The thickness is in the range of more than 50 μm and not more than 450 μm, An adhesive film having a tensile modulus in the range of 1.0 GPa or more and 1.2 GPa or less, and a storage modulus at 80°C in the range of 10 MPa or more and 20 MPa or less.
Citation Information
Patent Citations
Metal-clad laminate sheet and circuit board
JP2018170417A